2021
DOI: 10.1152/ajpheart.00036.2021
|View full text |Cite
|
Sign up to set email alerts
|

Racial and socioeconomic disparity associates with differences in cardiac DNA methylation among men with end-stage heart failure

Abstract: Heart Failure (HF) is a multifactorial syndrome that remains a leading cause of worldwide morbidity. Despite its high prevalence, only half of HF patients respond to guideline-directed medical management, prompting therapeutic efforts to confront the molecular underpinnings of its heterogeneity. In the current study, we examined epigenetics as a yet unexplored source of heterogeneity among patients with end-stage HF. Specifically, a multicohort-based study was designed to quantify cardiac genome-wide cytosine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 83 publications
1
14
0
Order By: Relevance
“…There is strong evidence that psychosocial stress resulting from structural racism differently predisposes African Americans to heart disease (Churchwell et al 2020). Recent studies have shown greater levels of CpG methylation in promoter regions of metabolic genes in heart muscle associated with heart muscle failure differentially by socially defined race and lower socioeconomic status (Pepin et al 2021). Thus, the historical presence of structural racism in America (both a social and physical environmental factor) is consistent with the long-standing disparity in heart disease by socially defined race.…”
Section: Diseases With Environmental Causesmentioning
confidence: 87%
“…There is strong evidence that psychosocial stress resulting from structural racism differently predisposes African Americans to heart disease (Churchwell et al 2020). Recent studies have shown greater levels of CpG methylation in promoter regions of metabolic genes in heart muscle associated with heart muscle failure differentially by socially defined race and lower socioeconomic status (Pepin et al 2021). Thus, the historical presence of structural racism in America (both a social and physical environmental factor) is consistent with the long-standing disparity in heart disease by socially defined race.…”
Section: Diseases With Environmental Causesmentioning
confidence: 87%
“…This and other examples highlight that, while often associated with a promise to disrupt fixed or typological identities (Malabou, 2016), an in-depth look at the way in which racial categories are operationalized in epigenetics research points to a more complex scenario. Only a limited number of studies are self-reflective about uncritical usage of racial categories, observing that "the use of race as a clinical proxy could perpetuate implicit racism in the healthcare setting" (Pepin et al, 2021(Pepin et al, : 2075. Although most studies build on pre-existing ethnic classifications for biomedical research (as highlighted in Table 1), they show little introspection or challenge to the validity and processes of social construction of these categories (one exception is Philibert et al, 2020).…”
Section: Synthesis Of Main Findingsmentioning
confidence: 99%
“…Only three articles (6%) mention or recognize the importance of wider socio‐structural factors as “drivers of racial health differences” (Pepin et al, 2021 ; see also Lynn et al, 2019 , Tsegaselassie et al, 2021 ). Reversibility is explicitly highlighted by 14 articles (28%) but most discussions of this are brief and often limited to the conclusion, with occasional reference to prospective pharmaceutical or therapeutic interventions (Chan et al, 2017 ; Demerath et al, 2015 ; Devaney et al, 2015 ; Enokida et al, 2005 ; Lynn et al, 2019 ; Okosun et al, 2000 ; Pepin et al, 2021 ; Pheiffer et al, 2020 ; Rai et al, 2019 ; Salihu et al, 2016 ; Tajuddin et al, 2019 ; Wang et al, 2016 ; Wiley et al, 2013 ; Zhu et al, 2016 ). v One significant exception is a study by Giuliani et al ( 2016 ) that emphasizes reversibility and variability as a theme throughout the article.…”
Section: A Scoping Review Of Environmental Epigenetics Dohad and Race...mentioning
confidence: 99%
“…It regulates chromatin architecture and transcription, and plays essential roles in a wide range of biological processes ( Li et al, 2013 ; Li et al, 2018 ; Roy et al, 2021 ). Accumulating evidence shows that the dysregulation of DNA methylation is involved in the development of many life-threatening diseases, including cancers, cardiovascular diseases ( Pepin et al, 2019 ; Heery and Schaefer, 2021 ; Pepin et al, 2021 ; Dillinger et al, 2022 ; Rosselló-Tortella et al, 2022 ). This Research Topic aims to elucidate the correlation between DNA methylation and human diseases, with the hope to deepen our understanding of the underlying molecular mechanisms of DNA methylation in human diseases and pave the way to the development of new strategies or methods for disease prevention, diagnosis, and therapy.…”
mentioning
confidence: 99%